Beyond Epinal Images: Neighborly Relationships in French Peri-urban Rural Communes - Charmes, Eric (Sociology of rural worlds in Poland and France: field research and studies, 2024)
In spite of profound transformations affecting rural worlds, i.e. a decline in the number of people working in agriculture; social reconfiguration marked by increased mobility and diminished specificity of rural lifestyle, the rural space continues to be entrenched in popular representations as an environment fostering strong community ties among its denizens. In stark contrast, peri-urban locales, often narrowly defined by individual housing and car dependency, are commonly perceived as spaces where neighborly relations tend to be limited. This article endeavors to nuance these simplistic portrayals by delving into the dynamics of two rural municipalities which recently became peri-urban: Marolles-sur-Seine (1800 inhabitants), situated in Seine-et-Marne, approximately 90 km from Paris, and La Bâtie-Montgascon (1900 inhabitants), located 70 km from Lyon. These two municipalities exhibit a distinctive characteristic emblematic of both peri-urban and rural landscapes ‒ namely, the prevalence of individual houses owned by their occupiers. Such individual housing is typically associated with a retreat into the domestic sphere and the cocooning comfort of the home. Yet, our inquiry substantiates a prior ethnographic research positing that neighborhood relations are far from nonexistent within low-density residential neighborhoods. Moreover, the survey results go further, revealing that, within Marolles and La Bâtie, such relations are notably more intense than in other contexts. Residential trajectories are a key explanation of this commitment to local sociability. Notably, individuals who have experienced upward mobility, particularly through homeownership, and households which have existed in these municipalities for a decade or more exhibit higher propensity for neighbourhood relations.